Cloudbursts : collected and new stories - McGuane, Thomas (Knopf, 2018)
"From one of our most acclaimed writers, a sumptuous gathering of his singular work in the short form, including seven new stories--nothing short of a literary event For more than four decades, Thomas McGuane has been heralded as an unrivaled master of the short story. Now the arc of that achievement appears in one definitive volume: thirty-eight stories drawn from his much-lauded previous collections, and another seven entirely new pieces appearing for the first time in book form. Set in the seedy corners of Key West, the remote shore towns of the Bahamas, and McGuane's hallmark Big Sky country, with its vast and unforgiving landscape, these are stories of people on the fringes of society, whose twisted pasts meddle with their chances for companionship. Moving from the hilarious to the tragic and back again, McGuane writes about familial dysfunction, emotional failure, and American loneliness, celebrating the human ability to persist through life's absurdities"--